Multilocus phylogenies reveal three new truffle-like taxa and the traces of interspecific hybridization in Octaviania (Boletaceae, Boletales) - Takamichi Orihara; Rosanne Healy; Adriana Corrales; Matthew E. Smith (IMA Fungus)
ABSTRACT Among many convergently evolved sequestrate fungal genera in Boletaceae (Boletales, Basidiomycota), the genus Octaviania is the most diverse. We recently collected many specimens of Octaviania subg. Octaviania, including several undescribed taxa, from Japan and the Americas. Here we describe two new species in subgenus Octaviania, O. tenuipes and O. tomentosa, from temperate to subtropical evergreen Fagaceae forests in Japan based on morphological observation and robust multilocus phylogenetic analyses (nrDNA ITS and partial large subunit [LSU], translation elongation factor 1-α gene [TEF1] and the largest subunit of RNA polymerase II gene [RPB1]). Based on specimens from the Americas as well as studies of the holotype, we also taxonomically re-evaluate O. asterosperma var. potteri. Our analysis suggests that O. asterosperma var. potteri is a distinct taxon within the subgenus Octaviania so we recognize this as O. potteri stat. nov. We unexpectedly collected O. potteri specimens from geographically widespread sites in the USA, Japan and Colombia. This is the first verified report of Octaviania from the South American continent. Our molecular analyses also revealed that the RPB1 sequence of one O. tenuipes specimen was identical to that of a closely related species, O. japonimontana, and that one O. potteri specimen from Minnesota had an RPB1 sequence of an unknown species of O. subg. Octaviania. Additionally, one O. japonimontana specimen had an unusually divergent TEF1 sequence. Gene-tree comparison and phylogenetic network analysis of the multilocus dataset suggest that these heterogenous sequences are most likely the result of previous inter- and intra-specific hybridization. We hypothesize that frequent hybridization events in Octaviania may have promoted the high genetic and species diversity found within the genus.